Strengthening community health volunteers as a community empowerment in the reduction of HIV/AIDS stigma - Rizka Ayu Setyani; Fika Lilik Indrawati (Journal of Community Empowerment for Health, 2020)
Negative stigma of society is one of the inhibitory factors of HIV/AIDS promotion and prevention programs. The Community Health Volunteer HIV (CHV HIV) program represents a community attempt to reduce the negative stigma of society concerning HIV/AIDS. The purpose of this activity is the formation of CHV HIV activities which are expected to educate the Primary Health Care (PHC) patients who are childbearing age women and expectant mothers in HIV/AIDS prevention; to support the success of the Prevention of Mother to Child Transmission (PMTCT) program; to increase the participation of childbearing age women and expectant mothers in Voluntary Counselling and Testing (VCT), and to reduce the incidence rate of HIV. Community empowerment activities were conducted in 2018, from July until November in Sleman, District Istimewa Yogyakarta (DIY). These activities involved the socialization of HIV/AIDS programs and education about VCT for CHVs in cooperation with PHC and non-government organizations (NGOs). The CHVs provided counselling for childbearing age women and expectant mothers related to prevention of HIV/AIDS transmission. The results of these activities were the increasing of CHV knowledge about HIV/AIDS and the formation of twelve CHV HIV in Sleman, DIY. In conclusion, this activity effectively increases the participation of childbearing age women and expectant mothers in voluntary HIV tests, so that the formation of CHV HIV could not only involve adult age volunteers but also adolescents.